Interactive Inflammatory Bowel Disease Biologics Decision Aid Does Not Improve Patient Outcomes Over Static Education: Results From a Randomized Trial. (10th September 2022) - Almario, Christopher V.; van Deen, Welmoed K.; Chen, Michelle; Gale, Rebecca; Sidorkiewicz, Stéphanie; Choi, So Yung; Bonthala, Nirupama; Ha, Christina; Syal, Gaurav; Dupuy, Taylor; Liu, Xiaoyu; Melmed, Gil Y.; et al.
Abstract : INTRODUCTION: To support shared decision-making (SDM) between patients and providers surrounding biologic treatments, we created IBD&me (ibdandme.org )—a freely available, unbranded, interactive decision aid. We performed a multicenter comparative effectiveness trial comparing the impact of IBD&me on SDM vs a biologics fact sheet developed by the Crohn's & Colitis Foundation. METHODS: We enrolled patients with inflammatory bowel disease (IBD) being seen at a clinic within IBD Qorus—a multicenter adult IBD learning health system—between March 5, 2019, and May 14, 2021. Eligible patients included those with recent IBD-related symptoms who reported that they wanted to discuss biologics with their provider during their upcoming visit. Patients were randomized 1:1 using stratified block randomization and received an e-mail 1 week before their visit inviting them to review either IBD&me or a fact sheet. The primary outcome was patient perception of SDM as measured by the 9-Item SDM Questionnaire (0–100 scale; higher = better); the Student t test was used to compare outcomes between arms. RESULTS: Overall, 152 patients were randomized (biologics fact sheet 75, IBD&me 77); most patients had Crohn's disease (66.4%) and were biologic-experienced (82.9%). No differences were seen between groups regarding SDM (fact sheet 72.6 ± 25.6, IBD&me 75.0 ± 20.8; P = .57). Most patients stated they would be likely to recommend the fact sheet (79.6%) or IBD&me (84.9%; P = .48) to another patient with IBD. DISCUSSION: No differences in outcomes were seen between IBD&me and the biologics fact sheet in this comparative effectiveness study; patients reported high satisfaction with both resources. Further study, particularly among biologic naïve patients, is needed to determine the utility of interactive components to IBD decision aids. Abstract :